VMP’s Micromobility on urban roads - Molina García, Pedro José (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
Urban Micromobility as a social and road reality can be estimated to be around five years old; although without abandoning the essence of the term, which continues to be applicable to any modality or means of personal transport that is carried out through very light vehicles, in this time technology has advanced at breakneck speed, offering multiple advantages, such as sustainability, comfort, independence, savings, etc., with respect to the traditional forms of displacement. However, the undoubted benefits that this implies are not exempt from important problems and difficulties, being especially noteworthy those related to daily road life among all users of public roads, manifested in a worrying way in the presence of these vehicles in the accident rate road. Within this evolution and sticking to the current situation, it is necessary to emphasize above all the Light Electric Vehicles (LEV), and more specifically the electric scooter, since it is the one that has achieved the greatest acceptance of all the devices powered by electric motor, having both the Legislator and the Administrations and society in general, openly face the unavoidable challenge of seeking and finding legislative formulas that guarantee peaceful and safe coexistence among all road users.